2018
DOI: 10.1681/asn.2017070774
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating Tissue-Resident Type 2 Innate Lymphoid Cells by IL-33 to Prevent Renal Ischemia-Reperfusion Injury

Abstract: The IL-33-type 2 innate lymphoid cell (ILC2) axis has an important role in tissue homeostasis, inflammation, and wound healing. However, the relative importance of this innate immune pathway for immunotherapy against inflammation and tissue damage remains unclear. Here, we show that treatment with recombinant mouse IL-33 prevented renal structural and functional injury and reduced mortality in mice subjected to ischemia-reperfusion injury (IRI). Compared with control-treated IRI mice, IL-33-treated IRI mice ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
166
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(176 citation statements)
references
References 56 publications
6
166
0
Order By: Relevance
“…In other studies, treatment with murine IL‐33, or recombinant human IL‐33 in humanized mice, prior to injury, induced similar protective effects, although only the day following injury was assessed . Loss of function studies were also performed by depletion of ILC2s in T/B cell‐deficient ( Rag1 −/− ) mice by treatment with anti‐CD90 . These studies demonstrated that the protective effects of IL‐33 were significantly diminished in the absence of ILC2s .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 90%
See 4 more Smart Citations
“…In other studies, treatment with murine IL‐33, or recombinant human IL‐33 in humanized mice, prior to injury, induced similar protective effects, although only the day following injury was assessed . Loss of function studies were also performed by depletion of ILC2s in T/B cell‐deficient ( Rag1 −/− ) mice by treatment with anti‐CD90 . These studies demonstrated that the protective effects of IL‐33 were significantly diminished in the absence of ILC2s .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 90%
“…These studies demonstrated that the protective effects of IL‐33 were significantly diminished in the absence of ILC2s . However, these mice were also depleted of other CD90 expressing cells including T reg cells, which may also be critical for this renoprotection . Furthermore, a complex bidirectional relationship exists between ILC2s and T reg .…”
Section: Ilc2s As a Potential Cellular Therapy In Renal Injurymentioning
confidence: 97%
See 3 more Smart Citations